AMILCAR CABRAL’S NOTES ON THE IMPASSES TO AFRICA’S DEVELOPMENT - Agbude, Godwyns Ade’; Adoba, Israel (European Scientific Journal, ESJ, 2014)
Development in Africa has been a consistent dialogue since the continent got independence. After the disengagement of the colonialists from the former colonies, development agenda has been set for Africa by both the ex-colonialists and the indigenous political leaders who inherited the colonial state. Amilcar Cabral is one of the theorists who engaged in a critical interrogation of the state of development in Africa. This paper focuses on exhuming two of the factors Cabral considered as impasses to Africa’s development. This paper also engages literature on Cabral and the speeches of Cabral where he bore his mind on development imperatives in the liberated zones which are replicas of the contemporary states in Africa. In other words, this paper dwells on secondary data analyzed through textual analysis. We finally arrive at the two monsters that have been standing as impediments to development in Africa.